679 Introduction of A Robotic Rectopexy Programme with Benchmarking to International Standards in Published Randomised Controlled Trials. (12th October 2021) - Wilkinson, G; Fleming, C; Brannigan, A
Abstract: Aim: With the evolution of robotic surgery, the adoption of a robotic approach to perform rectopexy, in particular ventral mesh repair (VMR), is gaining popularity. We aimed to audit clinical outcomes following introduction of a robotic rectopexy (RR) programme and compare outcomes to internationally published randomised controlled trials (RCTs). Method: Consecutive patients undergoing RR from July to December were included. The daVinci Xi surgical system (Intuitive, California) was used for all procedures using a modified left lower abdominal approach. Where VMR was performed, a 4 x 18cm Permacol mesh was used as standard and posterior fixation using ethibond. We compared operative times and 30-day clinical outcomes to international data. Results: Over a six-month period, thirteen RR were performed (n = 1 sutured, n = 2 resection sutured, n = 10 VMR). All patients were female with a mean age of 60.4 years (SD 14.12). Mean time from 1st consultation to surgery was 10.7 months. Three patients had an external rectal prolapse and ten patients a rectocoele confirmed on dynamic MRI. Seven patients had co-existing urinary symptoms impacting on quality of life. Median docking time was 23 minutes and median robotic operative time was 194 minutes (156 minutes reported). There were no conversions (2.5% reported). Average length of stay was 5 days (4 days reported) and there were no 30-day morbidities (8.6% reported) or readmissions. Conclusions: Robotic rectopexy can be performed with appropriate operative times and clinical outcomes and offers a superior operative platform for critical operative steps including rectal mobilisation and VMR mesh placement and suturing.